Efficient Attribute-Based Encryption Schemes for Secure Communications in Cyber Defense. Issue 3 (2nd July 2016) - Mao, Yijun; Zhang, Yue; Chen, Min-Rong; Li, Yongbiao; Zhan, Yiju
Abstract: How to securely transmit data over the cyber is an important problem in cyber defense. In this paper, we propose a ciphertext-policy attribute-based encryption (CP-ABE) scheme, in which the messages are encrypted together with access policy, while secret keys are associated with specified sets of attributes, and the secret keys can correctly decrypt the ciphertexts only when the attributes satisfy the associated access policy. Our proposed CP-ABE scheme is provably secure in the full model without random oracles, and has a tight security reduction. We stress that a tight security reduction implies a higher security or the requirement of smaller keys and ciphertext sizes to obtain the same security level, and thus make the scheme more efficient. Thus our scheme can be efficiently used to encrypt the transmitted data over cyber in a fine-grained manner.